2018
DOI: 10.3846/jcem.2018.457
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mechanical Properties of High Strength Concrete (Hsc) After Exposure to High Temperature

Abstract: There has been a tendency to design ever slender building construction using high strength concrete in recent years. Application of HSC is also growing in tunnel construction. One of the most important challenges is to control explosive spalling of concrete and the method recommended by Eurocode 2 (EN 1992-1-2:2008/NA:2010P) is addition of polypropylene fibres to the mix. The purpose of the research described in this paper was to evaluate the changes of mechanical properties of HSC exposed to the effect of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Studies on the fire performance of concrete have shown that, compared to building materials such as steel and wool, concrete demonstrates the best fire resistance [131]. The addition of reinforcements further increases the thermal stability of the concrete.…”
Section: Fire Propertiesmentioning
confidence: 99%
“…Studies on the fire performance of concrete have shown that, compared to building materials such as steel and wool, concrete demonstrates the best fire resistance [131]. The addition of reinforcements further increases the thermal stability of the concrete.…”
Section: Fire Propertiesmentioning
confidence: 99%
“…It can be found almost anywhere in human existence. However, due to their brittle characteristics, concrete structures are prone to damage, especially cracks, under the influence of harsh environments, external loads, or fire [ 2 , 3 , 4 , 5 ]. The appearance and expansion of cracks can have a negative impact on the mechanical properties and durability of cement-based materials [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, improved fracture toughness, impact resistance, ductility, tensile and bending capacity are leading to an increase in applications of polypropylene FRC [7,16,17]. Polypropylene fibres also increase thermal stability and improve the properties of concrete samples exposed to elevated temperatures [18][19][20]. Fibres are divided into two categories by their size, specifically, micro and macro fibres.…”
Section: Introductionmentioning
confidence: 99%